Safe Dishwashing Without an Automatic Dishwasher for Home, Community Events, and Outdoor Activities - Morgan Denhard; Amy Simonne; Ricki McWilliams (EDIS)
Most of us are accustomed to the ease and convenience of washing our dishes in an automatic dishwasher. At times, however, no dishwasher is available. This 4-page fact sheet teaches ways to safely wash or clean your dishes by hand, which may be necessary when your dishwasher is broken, you are outdoors, or you are working in a facility without a dishwasher. Written by Morgan Denhard, Amy Simonne, and Ricki McWilliams, and published by the UF Department of Family, Youth and Community Sciences, December 2013.